Answer:
-3(x-5)(x+2)
Step-by-step explanation:
the generic form of a second degree equation is:
y = ax^2 + bx + c
with "a" = -3, we have y = -3x^2 + bx + c
for y=0 (x-intercepts), we have x = -2 and x = 5, so:
1: 0 = -3*(-2)^2 + b*(-2) + c
-12 -2b + c = 0
-2b + c = 12 (eq1)
2: 0 = -3*5^2 + b*5 + c
-75 + 5b + c = 0
5b + c = 75 (eq2)
doing (eq2) - (eq1), we have:
7b = 63 -> b = 9
using b = 9 in (eq1), we have:
-18 + c = 12 -> c = 30
so, the equation is y = -3x2 + 9x + 30
in factored form: y = -3(x2 - 3x - 10) = -3(x-5)(x+2)